PENGARUH EKUITAS MEREK DAN RASA PERCAYA DIRI KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN SARUNG BHS (Studi Kasus pada Toko AL- Bagdadi) - Nurdiansyah, Chepi (Jurnal Komunikasi, 2018)
Abstract-Since 1953 PT BEHAESTEK contribute as resulting in the production of industrial textiles such as woven sarongs who have various kinds of colors and an interesting motif . BHS sheath is woven songket sarong which has a wide variety of motifs and attractive colors in the mix with woven embroidery adorn each sheath makes the sheath BHS become a premium product. The brand can be interpreted as a name representing the product as a whole. Brand equity is the value given on the product and services. Customer awareness of the quality of a brand, showed the presence of the brand uniqueness compared to other brands. This causes customers have reason to buy these brands (reason to buy) and have an impact on the incidence of confidence over the purchase decision. This study analyzes the influence of the elements of the brand equity Of the confidence The Customers purchasing decision sarung BHS. This research uses a multiple linear regression analysis to assess the effects of brand equity and confidence towards sarung purchasing decision BHS. As a result, brand equity and beliefs affect the purchasing decision sarung BHS. Variable beliefs have a dominant influence on purchasing decisions.Â Keywords: Brand Equity, Price, Product Quality and Purchasing Decision